Optimized pointing to improving the performance of optical metro networks based on mono-static free-space-optical transceivers - López-Leyva, Josué Aarón; Talamantes-Álvarez, Ariana; Ramos García, V.M.; Ponce Camacho, Miguel Ángel; Estrada-Lechuga, Jessica; Mejía González, Efraín Atenógenes (My University, 2019)
The performance and reliability are crucial features of the FSO links involved in optical metro networks (particularly, for last mile networks). In particular, the performance of the overall optical communication system depends on the process of tracking, acquisition, and pointing between the transmitter and the receiver. However, the optimization of these processes is required in order to reduce the resources and maintain a particular performance. In this paper, we propose an optimized method for the pointing process by directly considering parameters highly related to performance (i.e. bit error rate and throughput) for different weather conditions. The proposal is focused on the emulated effects of the pointing error angles of the transmitter and the receiver in the signal to noise ratio. The results showed that the performance of the FSO link remains constant ( ≈10 -9 ) for different weather conditions (from clear air to extreme rain, 3 dB and 10 dB, respectively). This performance is based on the adequate choice of the error pointing angles related to the diameters of the telescopes used. Finally, the optimized pointing process permits to relax the design of conventional pointing systems since the proposal is not based on the quality of the image spot, the sensitivity of the position sensing diode, among other parameters considered by conventional systems.
Scopus
Keywords: Free space optical link; Pointing error angle; Optimized pointing process; Sistemas